Synthesis and Cholinesterase Inhibitory Potency of 2,3-Indolo-oleanolic Acid and Some Related Derivatives - Anastasiya V. Petrova; Irina V. Zueva; Konstantin A. Petrov (Molbank, 2023)
In this study, the synthesis and biological activities of previously and newly synthesized oleanolic acid derivatives containing seven-membered cyclic amines at the C28 position were described. The obtained compounds were fully characterized via 1H and 13C NMR spectroscopy, and the bioactivity was evaluated by Ellman’s method. Among the tested compounds, 2,3-indolo-oleanolic acid was found to be the most active compound with an IC50 value of 0.78 µM against acetylcholinesterase. These results are significant due to the fact that research on the inhibition of acetylcholinesterase and butyrylcholinesterase enzymes by oleanolic acid, in particular indoloderivatives, is limited.